Improving integrated pest management of wheat stem sawfly (Hymenoptera: Cephidae) - Peirce, Erika S., author; Ode, Paul, advisor; Peairs, Frank, advisor; Rand, Tatyana, committee member; Haley, Scott, committee member (Colorado State University. Libraries, 2021)
The wheat stem sawfly (Cephus cinctus Norton) has been a major pest of cultivated wheat (Triticum aestivum L.) for over 100 years. It is difficult to estimate the damage of this insect. Still, conservative calculations estimate the grain-yield loss to exceed 30%, and the economic losses exceed $350 million annually in affected regions in the United States of America. This estimate does not include Colorado, so we expect the current figure to be much higher. Most economic loss is caused when the larva reaches the final instar when it creates a hibernaculum (stub) by cutting the stem above ground level just before harvest, which causes the wheat stem to fall. Fallen stems are difficult to harvest and are easily blown away. The life cycle of this pest makes it difficult to control, and current management strategies are not always effective. My dissertation aims to improve current integrated pest management strategies to control the wheat stem sawfly better. Chapter 1 briefly introduces the three aspects of integrated pest management that I studied: plant resistance, biological control, and cultural control using trap crops. Breeding for host-plant resistance is of particular importance for the management of wheat stem sawfly and is often considered the most effective. In Chapter 2, I review the current literature on plant resistance to the wheat stem sawfly. First, I examine host plant resistance using solid pith expression. Solid pith expression is the most common mechanism of resistance to the wheat stem sawfly. However, expression and control are inconsistent and often impacted by environmental variables. Another drawback to solid stemmed varieties is how biological control can be affected by solid stem expression. Next, moving away from the solid stem, I explore the literature on resistance due to host-preference and new resistance mechanisms derived from wheat landraces. I conclude this chapter by suggesting improvements to breeding for wheat stem sawfly resistance, such as screening for resistance and a deeper analysis of host plant metabolism. Given the variability of current resistant genotypes, I developed a new screening method for resistance described in Chapter 3. I report a novel screening method where plants are grown in the greenhouse in conetainers under optimal conditions and then subjected to a natural infestation in the field. Using this method, I was able to examine host preference as well as host suitability. For this experiment, I chose seven winter wheat genotypes with different levels of pith expression to measure host preference and suitability and compared results to field trials. Results of the conetainer study showed similar sawfly infestation amounts as those observed in the field study, which confirms the robustness of the conetainer assay. In addition, the smallest larvae and lowest infestation amounts were found in a solid-stemmed variety in 2019 and a semi-solid stemmed variety in 2020. This screening method will allow wheat breeders and entomologists to evaluate host plants for various resistance traits gather information on host preference and suitability. The wheat stem sawfly can be successfully controlled by biological control. However, in Colorado, we have not observed high populations of the common biological control agents of the wheat stem sawfly. Chapter 4 examined the prevalence of two Bracon parasitoids, Bracon cephi Gahan and B. lissogaster Muesebeck, and their host the wheat stem sawfly. I assessed the degree of non-crop and crop host plant use and responses to landscape composition. I also found no parasitism by either Bracon species in our three-year statewide winter wheat survey. Still, I found small populations of Bracon in non-crop landscapes throughout eastern and western Colorado. I used model selection to examine how local (500 m scale) and landscape (5 km scale) cover of suitable non-crop and crop habitats potentially affect Bracon and wheat stem sawfly abundances. My best fit model for wheat stem sawfly suggests that a decrease in non-crop cover at the landscape scale increases wheat stem sawfly infestation in non-cultivated grasses. My best fit model for Bracon parasitism suggests an increase in wheat cover at the local level results in the greatest increase in the odds of parasitism by either species of Bracon. Herbaceous cover at local and landscape scales were also significant predictors of Bracon parasitism. This study suggests that pests and natural enemies respond differently to landscape composition, and these responses should be evaluated before management decisions are made.
Keywords: habitat management; integrated pest management; wheat stem sawfly; host-plant interactions; biological control; survey